Problem mezolitu w Sudetach - Bronowicki, Jarosław; Bobak, Dariusz (Instytut Archeologii i Etnologii PAN, 1999)
The problem of the Sudety Mountains as a territory ofMesolithic settlement has arisen only during last few years. The Sudety issue has not been dealt with in any particular way as far as the Czech part of the mountains is concerned due to the fact that the country is situated entirely in the upland and mountainous area of Central Europe. Until recently sites in the Polish part have not been known at alL After they were discovered it proved to be necessary to treat the Mesolithic period in the Sudety distinctively from the Lowland studies, and therefore the Sudety macroregion of Mesolithic settlement was introduced. At the present stage of research it appears that the Sudety were inhabited mostly by societies of Western Mesolithic technocomplex. Nearly all sites from today's Czech Republic and some Polish sites (such as Ratno Dolne 2, Radzikowice) can be related to the Beuronien; apparently the Sowie Mountains microregion of Mesolithic settlement was strongly influenced by the Beuronien, which implies possible cultural overlapping with a similar nature to the Fien group. At the same time the north parts of the Sudety were exploited by groups of Lowland origin, mostly from the Komornica - Duvensee technocomplex (such as Grodziszcze 7, Jeglowa 2). Numerous materials characteristic of Janislawice culture were found at the site ofGrodziszcze 7; their position, however, is not entirely clear (cultural influence or separate settlement stage). The earliest penetrations of Mesolithic population can be dated to the Boreal period (Orlice Mountains settlement microregion, Ratno Dolne 2), yet the largest development of the settlement can be observed during the Atlantic period. It is most probable that Mesolithic societies were functioning in the Sudety at the time when early agriculture settlements were expanding in loess areas. The Baltic erratic flint, which was imported to the south beyond its deposit range in fluvioglacial and moraine formations of the north part of the Sudety, was used as predominant raw material for tool production. A wide range of local non-flint materials was used as well, even in areas abundant in erratic flint. This fact may be considered to be the basic feature of the Sudety Mesolithic specificity, similarly to a prevailing tendency to locate the sites on heavy clay soils, which were generally avoided by Lowland communities.
Mesolithic issue in the Sudety Mountains
Keywords: Mesolithic; Southern Poland; Silesia; Central Europe; Sudetes; mezolit; Polska południowa; Śląsk; Europa Środkowa; Sudety; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology